Resilience as a Buffering Variable Between the Big Five Components and Factors and Symptoms of Academic Stress at University - de la Fuente, Jesús; González-Torres, María Carmen; Artuch-Garde, Raquel; Vera-Martínez, Manuel Mariano; Martínez-Vicente, Jose Manuel; Peralta-S'anchez, Francisco Javier (Frontiers in Psychiatry, 2021)
The aim of this cross-sectional study was to establish predictive relationships of the Big Five personality factors (according to their self-regulatory level), together with resilience (proactive and reactive factors), for factors and symptoms of academic stress related to teaching and learning in the university context. A total of 405 female undergraduate students were selected, and completed questionnaires that had been previously validated in Spanish university students (Big Five personality factors, resilience, and academic stress symptoms and factors). A linear, ex-post facto design was used, including linear regression, Structural Equation Modeling (SEM), and mediational analyses. Specific linear regression showed the expected gradation: that self-regulatory personality factors (conscientiousness, extraversion) were positive linear predictors of proactive resilience, as well as significant negative predictors of stress factors and symptoms of academic stress; while the nonregulatory personality factors (openness to experience, agreeableness) showed little relationship. By contrast, the dysregulatory personality factor (neuroticism) was a negative predictor of proactive resilience, a positive predictor of reactive resilience, and positively predicted academic stress factors in the teaching and learning process, as well as stress symptoms. SEM general analysis showed that personality factors positively predicted resilience, and resilience negatively predicted factors and symptoms of academic stress. Specific mediational model analysis, with each personality factor, confirmed the different mediating relationships that appeared in the linear regression analyses. These results are discussed from the perspective of promoting resilience and healthy personalities in the university context. Implications for addressing academic stress at university are discussed.